Crimes against personal privacy in the context of artificial intelligence in Colombia - Gustavo Andrés López Rincón; Laura Marcela Quintero Sánchez (Postulados: Revista Sociojurídica)
This document describes the evolution of Colombian legislation regarding computer crimes, based on the mechanisms in the use of new technologies and the resulting vulnerability for Colombian state partners in the use of these tools, against fundamental rights for the enjoyment of a dignified life such as privacy. At the same time, we can find the most relevant legislation regarding the protection of the right to privacy in Colombia and what the use of artificial intelligence means in our society and what is the protection of the right to privacy through artificial intelligence applications